PENGARUH HIPERTENSI ESENSIAL TERHADAP PENYKIT JANTUNG KORONER MENGGUNAKAN PEMODELAN FUNGSI TRANSFER - Yusrina Dirayati Hermanto; Mahmudah Mahmudah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2016)
Objective: Modeling of the transfer function is now widely used in research in economics and agriculture, but the use of the health sector it is still a little bit. Therefore in this study applied modeling the transfer function of CHD cases in the province of East Java. Methods: Modeling of the transfer function is a model that illustrates that the predictive value of a time series (output atauY_t) based on past values of the time series itself and based on a time series data related to input or output X_t the series. This study uses secondary data obtained from the Health Department of East Java Province from January 2010 until August 2015 with quantitative research methods are modeling the transfer function of single input in order to get transfer function model which is applied to the cases of CHD by seeing how much influence a case essential hypertension to CHD by a certain time. Results: The results show that there is a significant positive effect on the occurrence of CHD is equal to 0.54631. Conclusion: Activities for regular blood checks are needed to reduce the increasing cases of CHD due to essential hypertension.